2010
DOI: 10.1111/j.1365-2648.2009.05244.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self‐efficacy, affectivity and collective efficacy on nursing performance of hospital nurses

Abstract: Understanding the effects of group-level variables on nursing performance improves performance management approaches in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
102
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 33 publications
12
102
1
7
Order By: Relevance
“…Burke, 1995;RiosRísquez, Mecca, & Fernandez, 2010;Salanova, Llorens, & Schaufeli, 2011;. Specifically, research (e.g., Carmeli et al, 2009;Fröjd & Von Essen, 2006;Lee & Ko, 2010) has shown that the performance of healthcare professionals depends in part on their effectiveness, their vigor, and their dedication. These positive states are reflected in the way healthcare workers treat patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Burke, 1995;RiosRísquez, Mecca, & Fernandez, 2010;Salanova, Llorens, & Schaufeli, 2011;. Specifically, research (e.g., Carmeli et al, 2009;Fröjd & Von Essen, 2006;Lee & Ko, 2010) has shown that the performance of healthcare professionals depends in part on their effectiveness, their vigor, and their dedication. These positive states are reflected in the way healthcare workers treat patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that work engagement has increased different health outcomes, such as: (1) business results (Harter, Schmidt, & Hayes, 2002), (2) performance and perceived quality of workers from various sectors (Burke, 1995;Rios-Rísquez, Mecca, & Fernandez, 2010;Salanova, Agut, & Peiro, 2005;Salanova et al, 2003), particularly in the healthcare sector (Carmeli, Ben-Hador, Waldman, & Rupp, 2009;Frojd & Von Essen, 2006;Koch & Jones, 2010;Lee & Ko, 2010), as well as (3) team performance assessed by the supervisor (Torrente et al, 2012), (4) levels of job control, positive affect, and efficacy beliefs in work teams as positive spirals (Llorens et al, 2007;Salanova, Llorens, & Schaufeli, 2011), (5) future academic success (Salanova, Martinez, & Llorens, 2012), and (6) job satisfaction and organizational commitment (Lebanon, Llorens, Bakker, Schaufeli, & Salanova, 2006) (for an in-depth review see: .…”
Section: Engagement In Teamworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, research (e.g., Carmeli et al, 2009;Fröjd & Von Essen, 2006;Lee & Ko, 2010) has shown that the performance of healthcare professionals depends in part on their effectiveness, their vigor, and their dedication. These positive states are reflected in the way healthcare workers treat patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that work engagement has increased different health outcomes, such as: (1) business results (Harter, Schmidt, & Hayes, 2002), (2) performance and perceived quality of workers from various sectors (Burke, 1995;Rios-Rísquez, Mecca, & Fernandez, 2010;Salanova, Agut, & Peiro, 2005;Salanova et al, 2003), particularly in the healthcare sector (Carmeli, Ben-Hador, Waldman, & Rupp, 2009;Frojd & Von Essen, 2006;Koch & Jones, 2010;Lee & Ko, 2010), as well as (3) team performance assessed by the supervisor (Torrente et al, 2012), (4) levels of job control, positive affect, and efficacy beliefs in work teams as positive spirals Salanova, Llorens, & Schaufeli, 2011), (5) Despite these advances, there is still a lack of studies that focus on the relationship between engagement in teamwork and service quality, particularly in the healthcare sector. One of the novelties of this study (besides the fact it assesses the relationship of personal resources at both the cognitive and the affective level with engagement) is the evaluation of service quality (in terms of performance, commitment, and perceived quality).…”
Section: Engagement In Teamworkmentioning
confidence: 99%